STUDY OF NODULATION AND NITROGEN FIXATION IN ANNUAL SPECIES AND VARIETIES OF VETCHLING, GENUS LATHYRUS - K. K. Sidorova; G. D. Levko; V. K. Shumny (Вавиловский журнал генетики и селекции)
The number of root nodules and nitrogen fixation rate (judged from nitrogenase activity) have been studied in nine varieties of five annual vetchling species: Lathyrus sativus, L. tingitanus, L. chlorantus, L. ochrus, and L. odoratus. All vetchling varieties are inferior to pea Pisum sativum in nitrogen fixation rate. A variation in nodulation pattern (nodule number, size, and location on roots) and nitrogen fixation rate among species and varieties has been detected. With regard to nitrogen fixation, Alisa and Nokturn varieties of sweet pea (L. odoratus) and Anna and Pink Flamingo of Tangier pea (L. tingitanus) deserve special attention.